PROBLEMATIKA KESEHATAN DI PESANTREN (SUATU KAJIAN PROSES DALAM PENDIDIKAN KESEHATAN BUDAYA DI PESANTREN X) - Muhammat Hidayat (Universitas Andalas, 2014)
Health is one of the basic human needs besides food, shelter and education in good health because only humans can live, grow and work better. Institute boarding school as a center of Islamic education has an important role in the process of empowering the nation not only in the field of Islamic Studies, and common areas, but also on the understanding that a healthy lifestyle and the health of its own. The problem faced is the boarding provision for the needs of the students studying in boarding schools, among other things, a place to stay (cabin), the provision of clean water needs for daily needs (drinking, eating, bathing, washing), latrines, and waste disposal of both solid and liquid. Problems in this paper, focused on boarding X, is; (1). How boarding X history? (2). How environmental health issues among students boarding-X ?. Study of the theory in this paper uses the approach of social health and social personality. Study focuses on hygiene in this study include; clean water, hygiene and sanitation facilities as well as the food habits of their boarding.